(untitled) (Al-Aasar, 2025)
This study examines religious guilt, shame and social acceptance from a psychological perspective within Muslim communities, specifically in Pakistan. The data was collected and analyzed using thematic analysis. The results illustrate how religious doctrine and social notions of what is "acceptable" overlap in defining individuals’ emotional experiences in terms of guilt and shame and how these emotions are related to mental well-being. The results revealed that guilt of religious origin, and often perceived as intentional and systematic guilt through faith (iman) and a course of repentance (tawbah), can be used as a positive tool of personal growth and correction. Precise social meanings regarding outward religious expectations and gendered expectations, contributed to individual level guilt and shame especially for women. Furthermore, the findings reveal the importance of hope in God’s mercy and having family support to carry the emotional load associated with guilt. The need for safe means to discuss emotional experiences and potentially avert feelings of shame and guilt and the call for more agency about the involvements of religious activity from both promoting justice, and mercy were evident in the study. Ultimately, the findings highlight the need for achieving mental well-being with ties to Islamic principles and these interventions should seek to target youth development of mental health.